olve for x: −2(3x−15)−4=56

.(1 point)
x=

1 answer

To solve the equation \(-2(3x - 15) - 4 = 56\), follow these steps:

  1. Distribute \(-2\) to the expression inside the parentheses: \[ -2 \cdot 3x + -2 \cdot -15 = -6x + 30 \] Therefore, the equation becomes: \[ -6x + 30 - 4 = 56 \]

  2. Simplify the left side: \[ -6x + 26 = 56 \]

  3. Subtract \(26\) from both sides: \[ -6x = 56 - 26 \] \[ -6x = 30 \]

  4. Divide both sides by \(-6\): \[ x = \frac{30}{-6} \] \[ x = -5 \]

Thus, the solution is: \[ \boxed{-5} \]